Analysis of Implementation of OSS-RBA Policy in Padang City - Ratih; Roni Ekha Putera; Hendri Koeswara (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
The research entitled Analysis of Implementation of OSS-RBA Policy in Padang City aims to analyze how the implementation of OSS-RBA Policy in Padang City uses the Van Meter and Van Horn implementation theory. The implementation of the OSS-RBA policy in Padang City has been carried out in accordance with the issuance of Mayor of Padang Regulation Number 73 of 2021 concerning Delegation of Authority to Implement Risk-Based Business Licensing and Non-Licensing to the Investment and One- Stop Service Office. This research uses a descriptive qualitative method with a phenomenological type. Research informants were determined by purposive sampling technique with data collection techniques through interviews and documentation. The results of the study indicate that the implementation of the OSS-RBA policy in the city of Padang has not gone well, because several variables according to the Van Meter and Van Horn Theory have not been fully achieved. The variables that have not been achieved consist of 3 variables in the form of standard variables and policy objectives, resource variables, and variables of economic, social and political conditions. Standard variables and policy objectives that are not in accordance with the needs of the Padang City DPMPTSP. The second variable is insufficient human resources both in terms of quantity and quality, as well as financial resources in the form of a budget that is not in accordance with the needs of the Padang City DPMPTSP. The third variable is social and political conditions that have not supported the implementation of OSS-RBA in Padang City. The recommendations given by the researcher are intended for the Padang City DPMPTSP Padang City government to provide additional documents and provide training for Padang City DPMPTSP employees regarding the implementation of OSS-RBA in the city of Padang so that the implementation of OSS-RBA policies can run optimally.